Development of pedagogical knowledge among learning assistants - Laken M. Top; Sarah A. Schoonraad; Valerie K. Otero (SpringerOpen, 2018)
Abstract Background Successful outcomes of the Learning Assistant (LA) model include increased learning outcomes in STEM gateway courses and increased persistence to graduation among LAs and the students they serve. While there are many possible reasons that the LA program is effective, the pedagogical development of the LAs themselves has not yet been systematically studied. The research reported here investigated how deeply first-time LAs enrolled in a one-semester pedagogy course took up the language associated with the course's essential pedagogical principles. By reviewing prior research as well as assessing our target population and our pedagogy course learning goals, we developed a set of three essential pedagogical principles that are critical for effective classroom instruction and developed a coding scheme for identifying these principles in LAs' written work. We then looked at LA's development of language with respect to these principles by analyzing weekly teaching reflections submitted by LAs during five iterations of our pedagogy course. Results Our research indicated that the language used to introduce particular pedagogical principles might play an important role in initiating LAs' uptake of these concepts. We found that LAs began to develop an understanding of the language that values students' prior ideas in learning, but the depth of this understanding varied. In addition, LAs did not demonstrate as much growth in their language with respect to the formative assessment or to the idea that students play a role in constructing knowledge. Conclusions In developing a pedagogy course for LAs, relating to their prior backgrounds in STEM appears to be critical. Using language that is accessible seems to increase LAs' ability to develop pedagogical principles. Although LAs' development of language related to the essential pedagogical principles is small, it may be enough to allow them to create contexts that facilitate learning.